If it's not what You are looking for type in the equation solver your own equation and let us solve it.
60=-10b
We move all terms to the left:
60-(-10b)=0
We get rid of parentheses
10b+60=0
We move all terms containing b to the left, all other terms to the right
10b=-60
b=-60/10
b=-6
| -4(2x+7)=-84 | | 3+8e=67 | | g(0)=3(0)-8 | | -4=-16+m/10 | | 3p+6+p-10=20 | | 4.6x=2.2x+24 | | 6x+8=-3x-6 | | -3(3s-4)-12=-2(6s+2)-3 | | 26=3.5+1.5(x-1) | | 2/5x-3=2-4/9x | | 295+31+b=360 | | 3t-2t=7 | | -m+7=12 | | 0.40x+0.05(16-x)=0.10(-48) | | -50+18=n | | -7x-9=28x-7(5x-9)= | | 13(n+11)=20n+59 | | 3t-3t=7 | | 8/9=88/x | | 6x-56=-4x+24 | | 6x+8÷7=-10 | | 4x+6=-93-5x | | 2k-5=8k+25 | | 6x+12=35 | | 12x^2-41x+70=0 | | 3(2x+5)=6(x-1) | | 5x+3+3x+9=180° | | 4/3x-8=52 | | 6x+8÷7=10 | | 5-8y=-5 | | 7/15=28/x | | -9+3x=7-5x |